TECHNOLOGY TRANSFER IN INDONESIAN STATE UNIVERSITIES: DO IPRS PLAY A SIGNIFICANT ROLE? - Asmoro, Puspa Kriselina (Indonesia Law Review, 2017)
The activity of knowledge and technology transfer from the academic side into businesses or the industrial sector through various schemes, so-called university technology transfer or academic technology transfer, involves a complex process of developing research ideas into the utilization of research. Historically, university technology transfer was triggered by amendment of the U.S. Patent Law, named the Bayh-Dole Act. Shortly after the amendment, technology transfer activity at U.S. universities escalated, particularly in patent and license activities. The movement of transfer technology was closed related to a research activity of the university and university patent in general. Through empirical study, this paper identifies technology transfer activities specifically on herbal pharmaceutical products at two Indonesian state universities, i.e. Institut Pertanian Bogor and Universitas Indonesia. The identification of technology transfer activity in both universities aims to study whether IPRs play a significant role in technology transfer activity.